2010
DOI: 10.2165/11538370-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness Without Head-to-Head Trials

Abstract: The absence of head-to-head trials is a common challenge in comparative effectiveness research and health technology assessment. Indirect cross-trial treatment comparisons are possible, but can be biased by cross-trial differences in patient characteristics. Using only published aggregate data, adjustment for such biases may be impossible. Although individual patient data (IPD) would permit adjustment, they are rarely available for all trials. However, many researchers have the opportunity to access IPD for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
215
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 283 publications
(216 citation statements)
references
References 35 publications
0
215
0
1
Order By: Relevance
“…9,12 However, methods that rely solely on aggregated data cannot fully adjust for baseline differences. 9,13 Ideally, individual patient data (IPD) should be available for each trial so to adjust for differences between trial populations using regression techniques. 13 However, access to all of the IPD for all of the trials is usually not available, and adjustment for observed differences between the trial populations using IPD from both trials is not conducted.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,12 However, methods that rely solely on aggregated data cannot fully adjust for baseline differences. 9,13 Ideally, individual patient data (IPD) should be available for each trial so to adjust for differences between trial populations using regression techniques. 13 However, access to all of the IPD for all of the trials is usually not available, and adjustment for observed differences between the trial populations using IPD from both trials is not conducted.…”
Section: Introductionmentioning
confidence: 99%
“…9,13 Ideally, individual patient data (IPD) should be available for each trial so to adjust for differences between trial populations using regression techniques. 13 However, access to all of the IPD for all of the trials is usually not available, and adjustment for observed differences between the trial populations using IPD from both trials is not conducted. 13 To overcome this, IPD from one of the comparator trials can be used to conduct a matchingadjusted indirect comparison (MAIC to adjust for baseline differences between trial populations by J u s t A c c e p t e d Curr Med Res Opin Downloaded from informahealthcare.com by Dicle Univ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases where trials of different treatments could be linked via direct comparisons to the same reference treatment, a network meta-analysis (NMA) was conducted to synthesize the direct and indirect evidence for each pairwise treatment comparison across included trials [28][29][30][31][32][33][34][35][36]. Matching-adjusted indirect comparisons (MAICs) were also used to compare outcomes across trials with adjustment for cross-trial differences in patient populations [37][38][39]. The MAICs utilized individual patient data (IPD) from DCV + ASV trials and aggregate data for comparator regimens including single-arm trials.…”
mentioning
confidence: 99%